2001
DOI: 10.1159/000050608
|View full text |Cite
|
Sign up to set email alerts
|

<i>bcl-2</i> Expression and Apoptosis in Primary and Metastatic Breast Carcinomas

Abstract: Objectives: To evaluate the role of bcl-2 and apoptotic index in the progression from primary to metastatic breast carcinoma and their influence on prognosis. Methods:bcl-2 expression was examined by immunohistochemistry and apoptotic index by in situ end-labelling in 116 surgical breast carcinomas and lymph node metastases from 50 patients. Results:bcl-2 was observed in 69 cases (59.4%) of primitive carcinomas and 26 cases (65%) of metastatic breast carcinomas and there was agreement of bcl-2 expression betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…In fact, p53 overexpression has been related to a high AI in breast [16,35] and ovarian carcinomas [36]. However, it should also be considered that in the present study p53 is related to proliferation and that proliferating tumors present high levels of apoptotic activity [37]. Thus, the close correlation between p53 and proliferation is in agreement with other reports [29,38].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, p53 overexpression has been related to a high AI in breast [16,35] and ovarian carcinomas [36]. However, it should also be considered that in the present study p53 is related to proliferation and that proliferating tumors present high levels of apoptotic activity [37]. Thus, the close correlation between p53 and proliferation is in agreement with other reports [29,38].…”
Section: Discussionsupporting
confidence: 92%
“…For example, the AIs are greater in lymph node metastases than in primary breast carcinomas [18], and AIs are also positively correlated with the pathologic grades of gliomas [19]. AI elevation has also been observed in the carcinogenesis of the endometrium [20] or the lung [21]; according to the observations of Törmänen et al, the demonstrated AI in these contexts also increased with the severity of the dysplasias that were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 and clusterin expression was scored as negative if no staining was seen, and positive if more than 10% of tumor cells showed staining. The selection of this cutoff value for clusterin and bcl-2 is based on previous reports [6,11,18] .…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…However, the prognostic significance of bcl-2 protein expression in tumor pathology is contradictory. Some authors have suggested a favorable prognostic role of bcl-2 positivity in breast and non-small cell carcinomas [11][12][13] while others have found a direct relationship between bcl-2 protein expression and a worse prognosis in prostate carcinomas and meningiomas [14,15] . However, the prognosis of bcl-2 expression has been reported in laryngeal carcinoma though with variable results [9,10,16] .…”
mentioning
confidence: 99%